TikTok shadows: unveiling the Abang Bas Sekolah grooming scandal - Shariffuddin, Norashikin; Zulkifli, Norsyazrah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In September 2024, a TikTok user known as “Abang Bas” was involved in a major child grooming and harassment case after posting videos of schoolchildren, particularly young girls, and referring to one as his “crush” and “darling.” The incident raised serious concerns about inappropriate online behavior. He was later arrested and charged under multiple Malaysian laws, including the Sexual Offences Against Children Act 2017 for sexual assault and grooming-related actions, the Child Act 2001 for publishing images of minors without consent, and the Communications and Multimedia Act 1998 for making derogatory remarks. He pleaded not guilty and was granted bail.